Taking proof-based verified computation a few steps closer to practicality - Setty, Srinath; Vu, Victor; Panpalia, Nikhil; Braun, Benjamin; Blumberg, Andrew J.; Walfish, Michael (USENIX Security, 2012)
We describe GINGER, a built system for unconditional, general-purpose, and nearly practical verification of outsourced computation. GINGER is based on PEPPER, which uses the PCP theorem and cryptographic techniques to implement an efficient argument system (a kind of interactive protocol). GINGER slashes query costs via protocol refinements; broadens the computational model to include (primitive) floating-point fractions, inequality comparisons, logical operations, and conditional control flow; and includes a parallel GPUbased implementation that dramatically reduces latency.